Preventive Strength of Dyadic Social Interaction against Reacquisition/Reexpression of Cocaine Conditioned Place Preference - Bregolin, Tanja; Pinheiro, Barbara S.; El Rawas, Rana; Zernig, Gerald (Frontiers in Behavioral Neuroscience, 2017)
The reorientation away from drugs of abuse and toward social interaction is a highly desirable but as yet elusive goal in the therapy of substance dependence. We could previously show that cocaine preferring Sprague Dawley rats which engaged in only four 15 min episodes of dyadic social interaction (DSI) did not reacquire and reexpress cocaine conditioned place preference (CPP) after a single cocaine exposure. In the present study, we investigated how strong this preventive effect of DSI is. In corroboration of our previous findings in rats, four 15 min DSI episodes prevented the reacquisition/reexpression of cocaine CPP in mice. However, this effect was only observed if only one cocaine conditioning session (15 min) was used. If mice were counterconditioned with a total of four cocaine sessions, the cocaine CPP reemerged. Interestingly, the opposite also held true: In mice that had acquired/expressed cocaine CPP, one conditioning session with DSI did not prevent the persistence of cocaine CPP, whereas four DSI conditioning sessions reversed CPP for 15 mg/kg intraperitoneal cocaine. Of note, this cocaine dose was a strong reward in C57BL/6J mice, causing CPP in all tested animals. Our findings suggest that both the reversal (reconditioning) of CPP from cocaine to DSI as well as that from DSI to cocaine requires four conditioning sessions. As previously shown in C57BL/6 mice from the NIH substrain, mice from the Jackson substrain also showed a greater relative preference for 15 mg/kg intraperitoneal cocaine over DSI, wheras Sprague Dawley rats were equally attracted to contextual stimuli associated with this cocaine dose and DSI. Also in corroboration of previous findings, both C57BL/6J mice and experimenters several generations removed from the original ones produced CPP for DSI to a lesser degree than Sprague Dawley rats. Our findings demonstrate the robustnuss of our experimental model across several subject- and experimenter generations in two rodent genus (i.e., mouse and rat) and allow the quantification of the strength (i.e., persistence) of the preventive effect of dyadic social interaction against the reacquisition/reexpression of cocaine CPP, arguably a model for cocaine relapse.